Phosphogypsum waste lime as a promising substitute of commercial limes: A rheological approach. (January 2019) - Romero-Hermida, M.I.; Borrero-López, A.M.; Alejandre, F.J.; Flores-Alés, V.; Santos, A.; Franco, J.M.; Esquivias, L.
Abstract: This paper presents the rheological properties of three types of lime putty, specifying the influence of their origin. The study aims to compare a special lime putty prepared from phosphogypsum with a commercial lime powder and an aged lime putty. The results obtained in terms of chemical composition, crystalline structure, grain size and rheological characterization, (linear viscoelasticity, shear rate and time-dependent flow behaviour) are presented in the study. Putties studied present a similar rheological response, which mainly depends on the particle size and water content. Lower values of the linear viscoelastic functions and viscosity were found for the phosphogypsum lime putty, in agreement with the higher particle size. Transient flow tests reveal a predominant elastic response with no significant shear-induced structural perturbations. However, either a thickening phenomenon over time, i.e. rheopexy, favoured at low shear rates, or a viscosity decrease, i.e. thixotropy, favoured at high shear rates, was observed.